Translating climate science into policy making in the water sector for the Vu Gia- Thu Bon River Basin - Tran, Tra Van (Technische Universität Dortmund, 2018)
Vu Gia- Thu Bon River Basin, located in the Central Coastal Zone of Viet Nam faces water shortage problems. This is expected to be further exacerbated in the future as a result of climate change. Previous attempts in addressing water shortage in the area followed a traditional top-down, predict-then-act approach. In such an approach, General Circulation Model outputs simulating future climate conditions are downscaled then adaptation measures proposed. This approach could produce optimal adaptation solution under an intended future. However, given the uncertainties related to GCMs, the approach fails to provide satisfactory information for adaptation measures. This study utilizes a combined top-down and bottom-up climate change impact assessment instead. A MIKE BASIN water balance model is used to analyze the water system response in the Vu Gia- Thu Bon River Basin under different rainfall and temperature ranges. Problematic conditions were then identified. Outputs from 25 GCMs were used to map the vulnerability space of the water system onto possible future climate conditions. A more detailed analysis of the system is thus performed only on problematic conditions suggesting both by the MIKE BASIN model and the GCM outputs. An analysis of the effects of current land use policy was performed to assist in the understanding of the changes in land policy and its effect on water usage. This was done through analyzing satellite images between the years 2011 and 2016 during the land use master plan period of 2011-2020. The results obtained in the study suggest that at a minimum, 66.36 km2 of agricultural area would be facing water challenges in the future. Under more severe climate change conditions, up to 87.77 km2 of crops would be facing water shortages. Overall, there is a water deficit of between approximately 11 million and 21 million m3 of water for agricultural production. To meet the demand, the study proposes two lines of action, namely conserve/reduce use of water, and production of additional water. Conserving/reducing water usage could be achieved through changing crop types, irrigation practice, and introducing water efficient technologies. On the other hand, production of additional water includes the construction of more water reservoirs as well as to look into options such as seawater desalination.
Keywords: Climate change; Bottom-up; MIKE Basin; Remote sensing; 710; Klimaänderung; Fernerkundung; Bottom-up-Prinzip; Wassermangel; Satellitenbild